Crime in second Polish Republic in the light of statistical data (Archives of Criminology, 2012)
After Poland regained independence in 1918, the system of crime statistics had to be organised from scratch and unified. At the same time, until new criminal code became effective, there were three criminal laws each of them with different scopes and forms of criminalization. Because of this in 1924 – 1934, crime statistics were based on classification drafted by the State Police Headquarters. Only since 1934 the statistics were base on the classification of the new criminal code. There was also a problem of separating statistical data concerning more serious crimes, defined by L. Radzinowicz as “true crime” from petty offences (which today are subject to Offences Code). As far as crime dynamics is concerned, the interwar period should be divided into three subperiods of 1924-1930, 1931-1934, and 1934-1938. In the first period crime intensity fluctuated yet with an overall increasing tendency. In 1931-1943 there was an explicit increase, particularly in 1931 and 1931. Reasons for this should be sought in the influence of the Great Depression. Since 1935 there was a decrease in reported crimes. In the last year of available statistics, that is 1938, crime level was 22,3% lower than in 1934. What draws one’s attention is the differences in reported crime levels before and after the war. Particularly, in the 1950s and 1960s crime levels were comparable to those in 1920s, that is before the Great Depression. It fell below this level only in 1970s, and in 1980s it increased again to the level comparable with 1920s. Reported crime levels throughout the period of communist Poland was however lower than in most of 1930s before the war. At the same time, it is clear that present crime levels are much higher than any of those in the interwar period. Data concerning intensity and dynamics of murders between 1924-1937 are particularly interesting. In 1920s number of murders increased similarly to increase of overall crime figures. After 1930 number of murders fluctuated only and its dynamics diverged from an explicit increase in overall crime. This fact made L. Radzinowicz conclude that the Great Depression – unlike it influenced crimes against property – did not influence violent crimes in an the same way. A decrease in violent crimes during an economic depression can be related, according to the author, with decreased alcohol consumption resulting from lower incomes of the population. There are many signs that murders are related to differences in the level of civilization, economic, and cultural life of particular parts of the country before the war and not to the economy cycle. What is interesting in the light of this is that the number of murders in post-war Poland never approached the number of crimes which were observed before the war. Dynamics of robbery was much different. Number of robberies in 1920s uninterruptedly decreased, and it increased since 1930s. But in comparison to the post-war period, robberies seem almost marginal.